Growth and molting of mud crab administered by different doses of vitomolt - Fujaya, Yushinta (Jurnal Akuakultur Indonesia, 2011)
Vitomolt is a molting stimulant made from spinach (Amaranthus spp.) extracts.  The objective of this study was to optimize the dose of vitomolt injection on the growth and molting of mud crab (Scylla spp). The research was conducted in April to June 2010.  There were three doses of vitomolt tested, i.e. 9 mg/g crab, 15 mg/g, and 21 mg/g crab. The results showed that the dose of vitomolt injection had great influence on the growth and molting of mud crab.  Higher dose of vitomolt gave higher growth but its molting percentage was different.  Vitomolt dose of 15 mg/g crab was the optimal dose to induce molting of mud crab while the dose of 21 mg/g crab gave the highest growth which reached 53.6%.  However, in terms of productivity, dose of 15 mg/g crab gave the highest production of soft crab. Key words: dose, vitomolt, growth, molting, mud crab   ABSTRAK Vitomolt adalah stimulan molting yang terbuat dari ekstrak bayam (Amaranthus spp.).  Tujuan penelitian ini adalah optimalisasi dosis penyuntikan vitomolt terhadap pertumbuhan dan molting kepiting bakau (Scylla spp).  Penelitian dilakukan pada bulan April hingga Juni 2010.  Ada tiga dosis vitomolt yang diuji, yakni: 9 mg/g, 15 mg/g, dan 21 mg/g kepiting. Hasilnya menunjukkan bahwa penyuntikan vitomolt sangat berpengaruh terhadap pertumbuhan dan molting kepiting bakau. Semakin tinggi dosis vitomolt memberikan pertumbuhan yang semakin tinggi pula namun tidak demikian terhadap persentase molting. Dosis vitomolt 15 mg/g kepiting adalah dosis optimal menginduksi molting kepiting bakau, sedangkan dosis 21 mg/g kepiting memberikan pertumbuhan tertinggi hingga 53,6%. Bila ditinjau dari produktivitas, dosis 15 mg/g kepiting memberikan produksi kepiting lunak tertinggi. Kata kunci: dosis, vitomolt, pertumbuhan, molting, kepiting bakau